The green inferno [videorecording (DVD)] - Izzo, Lorenza, 1989-; Levy, Ariel; Burns, Aaron, 1985- (Universal Studios Home Entertainment, 2016)
A group of student activists travels to the Amazon to save the rain forest and soon realize that they are not alone, and that no good deed goes unpunished.